Republic of Kazakhstan : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The staff report for the 2005 Article IV Consultation on the Republic of Kazakhstan highlights the economic outlook and fiscal policy. Inflation moderated to single-digit levels and confidence in the banking system strengthened, leading to rapid remonetization and significant dedollarization. The conduct of monetary policy has been complicated by the inflows of private capital, surging oil earnings, and buoyant demand conditions. Although Kazakhstan has made considerable progress in the structural area, the pace of reform implementation has slowed. Rapid growth has translated into lower poverty, but social indicators remain weak.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet